Revealing Economic and Racial Injustices: Demographics of Abortion Fund Callers on the U.S.–Mexico Border. Issue 3 (3rd July 2021) - Leyser-Whalen, Ophra; Torres, Luis; Gonzales, Brianna
Abstract: There are multiple accessibility challenges to abortion care in the United States. Most abortion research relies on clinic data, whereas we utilized data from an abortion fund on the U.S.–Mexico border. The majority of the sample were Latinx (62.2%), were 20–29 years old (59.7%), were in the first trimester (65.4%), and traveled hundreds of miles to an abortion clinic. Younger age, being in the third trimester, not having insurance, and having some resources were associated with likelihood of receiving aid for an abortion procedure. There is still a great need for abortion funding and access, particularly for young, economically disadvantaged people of color.